Hunger, undernutrition, and other forms of malnutrition from the perspective of achieving human rights: A critical essay - de Oliveira, Maria Rita Marques [UNESP] (FapUNIFESP (SciELO), 2024)
Objective This article critically evaluates how hunger and malnutrition have been addressed in the international context and Brazilian public policies from the perspective of human rights and in the face of a post-COVID-19 pandemic reconstruction and political crisis. Method It is a critical essay based on experiences and research in the author’s collection, complemented by a random search in other databases. The text is a historical-critical perspective referenced in Morin’s contributions regarding planetary complexity. Result The theme is introduced based on the main historical markers in the evolution of consensus regarding the Human Right to Adequate Food and the struggles for its achievement, followed by four sessions: hunger and malnutrition as a violation of the Human Right to Adequate Food; global overview of hunger and malnutrition in the context of the food system; an international strategy to ensure the Human Right to Adequate Food; the enforceability of the Human Right to Adequate Food in Brazil. Conclusion Given the social, cultural, economic, and political context that we find ourselves in, the prognoses indicate that we will not be able to fulfill the commitment made by 2030, hence the importance of a new social pact towards a socially, environmentally, and economically sustainable future for the full realization of rights and sustainability of life on the planet.
Fome, desnutrição e outras formas de má nutrição na perspectiva da realização dos direitos humanos: um ensaio crítico
Keywords: Alimentos; Direitos Humanos; Food; Food system; Human rights; Nutrition; Nutrição; Sistema alimentar